HPV and Systemic Response in Cervical Intraepithelial Neoplasia - Silva, Bianka de Oliveira; Gomes, Patrícia Oliveira Emerich; Mantovani, Priscila Thais Silva; Vieira, Jéssica Ferreira; Jammal, Millena Prata; Michelin, Márcia Antoniazi; Macêdo Barcelos, Ana Cristina; Murta, Eddie Fernando Candido; Nomelini, Rosekeila Simões (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Objectives: to verify whether there is an association of low and high-risk HPV with blood count parameters in patients with cervical intraepithelial neoplasia. Methods: We prospectively evaluated 48 patients with Pap smear showing low or high-grade intraepithelial lesion, submitted to collection of material to perform PCR for high-risk and low-risk HPV. The following blood count parameters were evaluated: hemoglobin, red blood cells, hematocrit, absolute number of leukocytes, neutrophils, lymphocytes, eosinophils, basophils, monocytes and platelets, neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and Red Cell Distribution Width (RDW). Receiver operating characteristic (ROC) curve was used to obtain the area under the curve (AUC) relating the positivity or not of HPV with the blood count parameters evaluated. Mann-Whitney test and multivariate analysis were performed, with level of significance less than 0.05. Results: Relating the positivity or not of HPV with the blood count parameters (Roc curves), there was statistical significance only between high-risk HPV and the platelet count (sensitivity=75%, specificity=66.7%, AUC=0.674, p=0.039). Platelet count ≤ 177,000/mm3 is associated with high-risk HPV. Subsequently, the multivariate analysis was performed, and the absolute value of platelets was considered an independent variable in this association with high-risk oncogenic HPV. Conclusion: A systemic response is found with the presence of high-risk HPV in CIN. Thus, platelet count ≤ 177,000/mm3 is associated with high-risk HPV.